Experimental investigation on expansive soils using electro kinetic geosynthetics (EKG) under cyclic loading. (2021) - Babu, Suresh; Thirumalai, R.; Naveen Nayak, V.; Gobinath, S.
Abstract: New applications for Geosynthetics have been identified if they can provide an active role, initiating biological, chemical or physical change to the matrix in which it is installed as well as providing the established functions. This can be achieved by combining the electro kinetic phenomena of electro osmosis, electrophoresis and associated electro kinetic functions such as electrolysis with the traditional functions of Geosynthetics. In this paper, a set of detailed experimental and software analysis is done on expansive soils (ie clay and block cotton soil) under various condition non saturated and fully saturated. Prototype of the cyclic loading disk (CLD) is designed, calibrated and installed. Soil samples are tested by using cyclic loading disk (CLD). For inducing Electro Kinetic Geosynthetics (EKG) effects and converting Alternate Current AC to Direct Current DC in soil samples, special electrical circuit is drafted from electrical CADD. Copper as Anode, Aluminium as Cathode and Perforated PVC tube as drain system. And Plaxis-3D software is used for analysis of soil in various conditions. As results and discussion obtained from the above made action, both expansive soils provides the good improvements from lateral sliding and shear strength parameters.